2020
DOI: 10.3390/children7110212
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Cause of Chronic Hypokalemia with Metabolic Alkalosis: Case Report and Differential Diagnosis

Abstract: Hypokalemia and metabolic alkalosis can be present in different rare diseases, and the differential diagnosis of these forms is challenging. Apparent mineralcorticoid (AME) excess syndrome is one of these conditions. Characterized by increased blood pressure due to excessive sodium retention and plasma volume, it is caused by a mutation in the HSD11B2 gene encoding the oxydoreductase enzyme 11β-hydroxysteroide dehydrogenase type 2. We report the case of a child presenting with failure to thrive associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…There was also a suspicion that the patient's presentation could be related to Liddle syndrome; however, the development of hypertension and hypokalemia during pregnancy and resolution thereafter inclined more toward the diagnosis of Geller syndrome. Reasons for not considering the other conditions that can present with hypertension and refractory hypokalemia as the cause of our patient's presentation are listed in Table 2 [ 1 , 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also a suspicion that the patient's presentation could be related to Liddle syndrome; however, the development of hypertension and hypokalemia during pregnancy and resolution thereafter inclined more toward the diagnosis of Geller syndrome. Reasons for not considering the other conditions that can present with hypertension and refractory hypokalemia as the cause of our patient's presentation are listed in Table 2 [ 1 , 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gitelman and Bartter syndrome can cause refractory hypokalemia as well; however, patients who are diagnosed with these syndromes have normal or low blood pressure with elevated renin and aldosterone levels [ 8 , 9 ]. Genetic testing remains the gold standard for confirmation of the diagnosis [ 1 ]; unfortunately, this was unavailable for our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Both mutations are characterized to result in Glu115 deletion, Leu116 deletion, a truncated 11 β HSD2 protein production, and Phe367 deletion. Moreover, Bertulli et al [ 28 ] reported that a novel homozygous frameshift variant in exon 5, c.900 dup, was found in a child with AME. In six affected patients from an Omani family, Yau et al [ 27 ] revealed that a homozygous c.799A > G mutation within exon 4 of the HSD11B2 gene is causing NAD misalignment under p.T267A substitution.…”
Section: Genetics Of Hypertensionmentioning
confidence: 99%
“…Severe AME is known to be correlated with IUGR since the deficiency of the 11β-HSD2 enzyme allows excessive amounts of maternal glucocorticoid to cross the placental barrier resulting in inhibition of fetal growth. 23…”
Section: Iugr Vs Hsd11b2 Gene Alterationmentioning
confidence: 99%